Stabilisation of compliant floating platforms with sheet barriers under wave action - Bi, Cheng (2022)
Excessive surface displacement of a compliant floating platform made of interconnected modular floats due to wave action can cause damage to the utility system (solar power, etc.) or endanger the safety of the service personnel on top. This study examines the use of a vertical tensioned sheet barrier installed in front of the floating platform for its stablisation under incident waves. Two configurations are investigated, namely finite and semi-infinite, representing a medium and large size platform respectively. Analytical analysis is performed without the pre-assumption of the dynamic behavior of the sheet barrier, and solutions are obtained using the eigenfunction expansion together with the least square method. For both configurations, the wave transmission to the floating platform reduces when the dynamic of the sheet barrier shifts from plate-like to membrane-like with increasing tension and also deeper draft and larger viscosity, which in turn reduces the platform displacement and the hydrodynamic pressure force on the platform. Overall, the results in the present study show that the installation of the barrier in front of the platform in the membrane-like hydroelastic regime with a penetration ratio more than ∼0.4 can significantly improve the stability of the compliant floating platform in the coastal environment.